The Procedure Applied in Translating Jargon in English Parliamentary Debating into Indonesian - Krisnawati, Ni Luh Putu (Lingual Journal of Language and Culture; Vol 3 No 1 (2017)DO - 10.24843/LJLC.2017.v03.i01.p07)
At present, competition regarding English debating is a common thing. All countries are competing in the World Debating Competition either for high school or university level. The spread of this “popular culture” has made other country to adopt the English debating system and translate that system into their native language. However it cannot be denied that there are also many jargons that need to be translated into the native language without changing the meaning. This research is focused on the jargons of the English parliamentary debating and its translation into Indonesia. The aims of this study are to identify the jargons in English parliamentary debating and its equivalence in Indonesia and also to know the procedures used in translating the jargons  in English parliamentary debating into Indonesia. The theory used for this study is the theory proposed by Peter Newmark (1988) regarding the procedure of translation. The findings shows that they are five procedure of translation used in translating the jargons of English parliamentary debating into Indonesia namely literal translation, functional equivalent, couplets, transference, and naturalization. Keywords: translation, English parliamentary debating, translation procedure